PEDAGOGICAL EXPERIENCE AND EFFECTIVENESS OF USING GAMIFICATION TECHNOLOGIES IN TEACHING HISTORY (Web of Teachers: Inderscience Research, 2026)
This study explores the pedagogical experience and effectiveness of implementing gamification technologies in history education. In contemporary educational contexts characterized by digitalization and learner-centered approaches, gamification has emerged as a powerful instructional strategy that enhances student engagement, motivation, and cognitive development. Drawing on the theoretical frameworks of John Dewey, Lev Vygotsky, and Karl Kapp, the research conceptualizes gamification as a pedagogical tool that integrates game elements into non-game learning environments. Using a qualitative and mixed-method approach, the study analyzes how gamification influences students’ historical thinking, motivation, and learning outcomes. The findings indicate that gamification significantly improves students’ engagement, critical thinking, and ability to analyze historical processes. The study concludes that gamification technologies, when applied systematically, enhance the quality of history education and contribute to the development of historical consciousness.